2011
DOI: 10.1007/s13173-011-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment-based influence detection on Twitter

Abstract: The user generated content available in online communities is easy to create and consume. Lately, it also became strategically important to companies interested in obtaining population feedback on products, merchandising, etc. One of the most important online communities is Twitter: recent statistics report 65 million new tweets each day. However, processing this amount of data is very costly and a big portion of the content is simply not useful for strategic analysis. Thus, in order to filter the data to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…These tweets contain a wide variety of information, ranging from conversational tweets to highly relevant information on specific topics [Bigonha et al 2012]. As a result, Twitter has become one of the most important mediums of communication.…”
Section: Identifying Topical Authorities In Microblogsmentioning
confidence: 99%
See 2 more Smart Citations
“…These tweets contain a wide variety of information, ranging from conversational tweets to highly relevant information on specific topics [Bigonha et al 2012]. As a result, Twitter has become one of the most important mediums of communication.…”
Section: Identifying Topical Authorities In Microblogsmentioning
confidence: 99%
“…(2) The Followers to Followees ratio (F-F ratio), that is, the number of a user's followers and the number of other people that the user follows (followees). As suggested in [Bigonha et al 2012], [Leavitt et al 2009], this metric valorises users who are widely followed, but have some selection for following others. In fact, the F-F ratio approaches infinity when the number of followers is very high and the number of followees is very low.…”
Section: Identifying Topical Authorities In Microblogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more recent literature has associated the complexity of the concept of influence with the diversity of content. Several research works have addressed the need for considering content-based metrics of influence (Bakshy et al 2011;Bigonha et al 2012;Hossain et al 2006;Li et al 2014;Naaman et al 2010). …”
Section: State Of the Artmentioning
confidence: 99%
“…Bigonha et al [3] found that the readability quality of a message was useful (along with network features ) in identifying the most influential members of a network. This stream of work has also been applied outside Twitter.…”
Section: Related Workmentioning
confidence: 99%